Clinical evaluation of DMARDs and NSAIDs in cases of Rheumatoid arthritis in Chhattisgarh - Basant Kumar Maheshwari (Asian Journal of Medical Sciences, 2018)
Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by polyarticular inflammation with systemic symptoms like malaise, fatigue and fever. Various groups of drugs have been used along with supportive therapies (physical and occupational) for the treatment of rheumatoid arthritis. Non-steroidal anti-inflammatory drugs (NSAIDs) and disease modifying agents in rheumatoid disease (DMARDs) are the two major classes among them. However, none of these medications have proved to be successful enough to be accepted universally as the standard therapy for RA.